Characteristics of stroke survivors in rehabilitation health organization, Kuala Nerus, Terengganu: A retrospective study - Aryati, Ahmad; Sakinah, Harith; Chin, Y.Y. (2017)
Stroke is the second leading cause of death after ischaemic heart disease worldwide and the third in Malaysia. The incidence and prevalence of stroke have increased dramatically in the past 5 years in Terengganu. Stroke event is life-changing to stroke survivors in terms of functional impairment, emotional, and communication skills. This study aims to describe various aspects of stroke such as diagnosis, previous history of stroke and multiple chronic conditions. In this community-based retrospective study, a total of one hundred and fifteen case records of stroke patients who previously attended Rehabilitation Health Organization, Kuala Nerus, Terengganu, starting from October 2013 until May 2017, were reviewed in this study. The socio-demographic and clinical information were assessed using medical folders. Descriptive statistics was performed using IBM SPSS version 21. Stroke patients consisted of 54 (47%) men and 61 (53%) women; with the median age of 61.0 ± 17.0 years (age range 26-83 years). Ischaemic stroke accounted for 80.0% in the cohort with slightly higher female proportion (55.7%), followed by haemorrhagic stroke (20.0%). Nevertheless, there was no significant association between gender and types of stroke (p> 0.05). A hundred patients (87.0%) had their first-ever stroke while 13.0% experienced the recurrent stroke. Patients with multiple chronic conditions were diagnosed to have diabetes mellitus and hypertension (31.3%), followed by hypertension (23.5%), and diabetes mellitus, hypertension and hyperlipidaemia (13.9%). These findings are essential for a reference in proper stroke management especially secondary prevention of stroke to reduce the burden of stroke as well as lower the stroke recurrence rate among stroke survivors.